Alexander and the terrible, horrible, no good, very bad day - Viorst, Judith; Cruz, Ray (New York : Atheneum Books for Young Readers, 2009)
On a day when everything goes wrong for him, Alexander is consoled by the thought that other people have bad days too.
"Special Limited Edition with a new preface by Judith Viorst and Ray Cruz."
Keywords: Humorous stories